Pengaruh Infusa Biji Buah Pinang (Areca catechu) Terhadap Tingkat Kematian dan Morfometri Cacing Dewasa Ascaridia galli Secara In Vitro - Wida Wahidah Mubarokah; Kurniasih Kurniasih; Wisnu Nurcahyo; Joko Prastowo (Jurnal Sain Veteriner, 2019)
The study evaluates in vitro effects of Areca catechu crude aqueous extract  as anthelmintics on Ascaridia galli adult mortality rate and morphometry. Naturally infected chickens were collected from slaughtered chickens at local slaughterhouses in Yogyakarta. Chicken’s intestines were carefully examined and transported to the Parasitological Laboratory of Gadjah Mada University, Yogyakarta. Ascaridia galli were collected from intestines (including duodenum, jejunum, and ileum) and put into a petri dish containing 0.62% saline water. There were 60 A. galli in each concentration of Areca catechu crude aqueous extract. Investigation on mortality rate of adult worms at various concentration and observation as well as differences in A. galli morphometry and mortality rate were analyzed using analysis Anova. The figures of the parasites or the parts of the parasites were captured using camera Lucida and then they were measured using both micrometer and curvimeter. The morphology of the parasites was identified to find out their morphometric characteristics.The results of morphometric observation of the A. galli showed that there was a significant difference in the body width and the vulva length of the females and in the body width, the esophageal length and the esophageal width of the males.This research disclosed that Areca catechu crude aqueous extract significantly affected the mortality rate of adult A.galli at various concentration. This research observed that the best concentration to kill the adult worms was 25% Areca catechu crude aqueous extract.